2019
DOI: 10.1002/aelm.201901143
|View full text |Cite
|
Sign up to set email alerts
|

Graphene/Au Hybrid Antenna Coil Exfoliated with Multi‐Stacked Graphene Flakes for Ultra‐Thin Biomedical Devices

Abstract: Flexible electronics with organic substrates have been developed for bio‐conformable devices and soft robotics. Although biodegradable polymers are preferred substrates for biomedical applications, they have poor heat durability, which precludes printing of conductive lines that require annealing at high temperatures (>250 °C). The fabrication of an ultra‐flexible, inkjet‐printed antenna coil with a resistivity of 4.30 × 10−5 Ω‐cm is reported. It involves annealing of a graphene/Au antenna coil printed on a gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…This value was within a range of those of typical commercially available coils that operate at similar frequencies ( q = 10–30) [ 37 ] and higher than those of previously reported thin‐film antennas made of finely‐patterned Cu wire ( q < 19), [ 11 ] 2D‐patterned liquid metal ( q < 5), [ 25 ] and inkjet‐printed Au/graphene ( q < 5). [ 16 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This value was within a range of those of typical commercially available coils that operate at similar frequencies ( q = 10–30) [ 37 ] and higher than those of previously reported thin‐film antennas made of finely‐patterned Cu wire ( q < 19), [ 11 ] 2D‐patterned liquid metal ( q < 5), [ 25 ] and inkjet‐printed Au/graphene ( q < 5). [ 16 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 4 ] 2D printing technologies permitted creating ultraconformable antenna based on sub‐micrometer‐thick conductive patterns on such polymeric ultrathin substrates. [ 16,17 ] However, 2D‐printed ultrathin antennas tend to be yet unsuitable for use on the wet and dynamic tissues in terms of limited electromechanical properties (i.e., poor stretchability and high resistance of the printed conductive patterns). Hence, to minimize the interference with the electrical and ionic conditions of the living physiological systems to the wireless operation, the integrated circuit must be sealed with an insulating layer (e.g., 50 μm‐thick silicone rubber sheet [ 16 ] ), which compromises the flexibility and conformability of the whole device.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported the transference of Au printed wirings to PDLLA thin film by utilizing the interlayer release of multistacked graphene flakes. [ 27 ] In this study, the printed wiring was directly transferred to the PDLLA thin film without using graphene. Our unique approach can lead to new fabrication methods of transferring metal particles onto various types of polymer thin films.…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported that a poly(D, L‐lactic acid) (PDLLA) nanosheet (thickness: 182 nm) can be employed as a base material of a wirelessly powered device. [ 27 ] PDLLA is a type of polymer that has biocompatibility, biodegradability, and heat resistance, [ 28 ] which has an ideal property in the fabrication process as well as practical application for hyperthermia. In this study, we developed a wirelessly operated, implantable IH device by layering thin‐film Au wiring (1.5 µm) and a biodegradable polymer thin film (5 µm) with a simple structure without consideration of the shape of the antenna, and the insertion of a resonant circuit ( Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Tetsu et al developed an ultra-flexible antenna coil through graphene/Au hybrid inkjet printing. [176] The graphene/gold bilayer spiral antenna coil is 24.96 cm in length and 5.5 turns in total, which was inkjet-printed into the glass substrate and transferred to polymer nanosheets, which is possible because graphene flakes are piled up with weak Van der Waals forces. [177] The electro-mechanical properties of the nanosheet antenna coil were evaluated through bending tests.…”
Section: Antennasmentioning
confidence: 99%